EU supports small hydropower in Central Asia - Jorde, K.; Alapfy, B.; Schwedhelm, H.; Siegfried, T.; Habersack, H.; Keyser, J. de; Hayes, D. S.; Purushottam, A.; Schneider, M.; Anarbekov, Oyture (2022)
Through the innovation project ‘Hydro4U’, the European Union (EU) under its Horizon 2020 funding scheme is funding the development and optimization of sustainable and practical technologies, planning methods and assessment tools in the area of small-scale hydropower with the primary goal to enhance their application in Central Asia. Thirteen partners, from the EU and from Central Asia, scientific institutions, consultants, industry partners and NGOs are collaborating over a period of five years to generate a sustainable impact on Central Asia by finding new ways to deal with the challenges that normally arise with hydropower development, covering technical, ecological, economic and social aspects.